Channel Selection and Contracting in the Presence of a Retail Platform - Shen, Yuelin; Willems, Sean P.; Dai, Yue (Production and Operations Management, 2019)
This paper studies how a manufacturer should engage with a platform retailer and a traditional reseller. Our work is motivated by the emergence of increasingly powerful retail platforms in China’s consumer electronics and appliances markets. The manufacturer pays a slotting fee and a portion of its sales revenue to the platform retailer in exchange for the opportunity to manage its own space within the retailer’s store. The manufacturer can also sell its product to a traditional reseller thereby earning its wholesale price. We first formulate a Stackelberg game where the platform retailer leads by setting the revenue‐sharing rate while the manufacturer follows by choosing to sell through one or both channels. We derive the equilibrium channel and characterize each party’s associated sales quantities, prices, and profits. After confirming, it is always beneficial for the platform retailer to determine the slotting fee and revenue‐sharing rate simultaneously, we then formulate two bargaining models between the manufacturer and the platform retailer. In the first model, they can negotiate just the revenue‐sharing rate and in the second they negotiate both the revenue‐sharing rate and the slotting fee. In the second model, a win‐win result for the manufacturer and platform retailer is possible. We find that the slotting fee is neither always beneficial to the platform retailer nor always harmful to the manufacturer; it depends on the demand substitution effect between the two retail channels.